Analisis Perencanaan Pembangunan Daerah dengan Pendekatan Sistem Lunak di Kabupaten Trenggalek - Lukiswara, Harendhika (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
This paper examine regional development planning process which is composing process for RPJMD documents of Trenggalek regency 2016-2021. In the process, composition RPJMD documents of Trenggalek regency have faced systemic, complex issues. To improve these complex issues, we used Soft System Methodology (SSM). Analysis result showed that composition processes for RPJMD documents of Trenggalek regency would consist of RPJMD initial design composition, RPJMD design composition, RPJMD musrenbang, RPJMD final design composition and regional regulation provision. This study conclude that there were 6 conceptual models to fix this issues, such as development planning approach model, inter-chapter relatedness model, planner and administrator relationship model, society’s participation model, document’s finalization model and political approach model.